The Role of Nitric Oxide in Stem Cell Biology - Estefanía Caballano-Infantes; Gladys Margot Cahuana; Francisco Javier Bedoya; Carmen Salguero-Aranda; Juan R. Tejedo (MDPI AG, 2022)
Nitric oxide (NO) is a gaseous biomolecule endogenously synthesized with an essential role in embryonic development and several physiological functions, such as regulating mitochondrial respiration and modulation of the immune response. The dual role of NO in embryonic stem cells (ESCs) has been previously reported, preserving pluripotency and cell survival or inducing differentiation with a dose-dependent pattern. In this line, high doses of NO have been used in vitro cultures to induce focused differentiation toward different cell lineages being a key molecule in the regenerative medicine field. Moreover, optimal conditions to promote pluripotency in vitro are essential for their use in advanced therapies. In this sense, the molecular mechanisms underlying stemness regulation by NO have been studied intensively over the current years. Recently, we have reported the role of low NO as a hypoxia-like inducer in pluripotent stem cells (PSCs), which supports using this molecule to maintain pluripotency under normoxic conditions. In this review, we stress the role of NO levels on stem cells (SCs) fate as a new approach for potential cell therapy strategies. Furthermore, we highlight the recent uses of NO in regenerative medicine due to their properties regulating SCs biology.